The Combination of Functional and Structural MRI Is a Potential Screening Tool in Alzheimer’s Disease - Huang, Chun-Chao; Huang, Wei-Ming; Chen, Chia-Hung; Jhou, Zong-Yi; The Alzheimer’s Disease Neuroimaging Initiative,; Lin, Ching-Po (Frontiers in Aging Neuroscience, 2018)
Introduction: This study aimed to survey the discrimination power of parameters from cerebrospinal fluid (CSF) biomarkers, fluorodeoxyglucose uptake on PET (FDG-PET), structural magnetic resonance imaging (MRI) and functional MRI in high and low risk subjects or in converters and stable subjects of normal and mild cognitive impairment (MCI) statuses. Methods: We used baseline resting-state functional MRI (rfMRI) from the Alzheimer’s disease neuroimaging initiative (ADNI) dataset to analyze functional networks and recorded subjects’ characteristics and results of CSF study, FDG-PET, and structural MRI from ADNI website. All parameters were evaluated between-group difference among normal (NC), MCI and Alzheimer’s disease (AD) groups. The parameters other than CSF results were included to study difference between high and low AD risk subjects in NC or MCI groups, based on CSF results. On the basis of two-year follow-up conditions, all parameters were compared between stable subjects and converters in NC and MCI. Results: CSF biomarkers, FDG-PET, structural MRI and functional MRI are all able to differentiate AD from MCI or NC but not between MCI and NC. As compared with low AD risk subjects, high-risk subjects present decreased FDG-PET in both MCI and NC groups but structural MRI change only in MCI status and rfMRI alteration only in NC status. As compared with stable subjects, converters have decreased FDG-PET, functional network changes and structural changes in both MCI and NC groups. Conclusion: The combination of functional and structural MRI is a safer screening tool but with similar power as FDG-PET to reflect CSF change in AD pathological process and to identify high-risk subjects and converters in NC and MCI.